Adaptive and diagnostic significance of the bark of Stryphnodendron polyphyllum (Leguminosae) from the Cerrado - Vergílio, Paula C. B. [UNESP]; Marcati, Carmen R. [UNESP] (CSIRO Publishing, 2017)
Bark comprises structurally and functionally complex plant tissues, providing a rich source of traits for taxonomic, phylogenetic, evolutionary and ecological studies. We compared bark traits of Stryphnodendron polyphyllum Mart. (Leguminosae) specimens growing in two Cerrado habitats (cerrado sensu stricto and gallery forest, being fire-prone and non-fire-prone habitats respectively), to determine which bark traits could be considered diagnostic and adaptively informative. We analysed the anatomy and thickness of the periderm, cortex, primary and secondary phloem, and also the bark histochemistry. Stryphnodendron polyphyllum is distinctive from other Stryphnodendron species reported in the literature, by the presence of a rhytidome, stratified lenticels and the non-collapsed parenchyma cells in the non-conducting phloem, which are, therefore, diagnostic traits for this species. Bark of S. polyphyllum showed a trade-off in resource allocation between the periderm and secondary phloem, whereas the thicker rhytidome seemed to be associated with fire protection in specimens from the fire-prone habitat, the wider sieve tubes in the thicker conducting secondary phloem indicated efficiency of photosynthate transport in the specimens from non-fire-prone habitat.
Keywords: gallery forest; phloem-transport efficiency; rhytidome